Application of interval analysis for improving reliability of estimation of hardness value spread for nuclear structural materials - Yefimov, A.V.; Potanina, Т.V. (Вопросы атомной науки и техники, 2020)
The applications of the interval and standard probabilistic approaches for verifying the reliability of the results of an experiment studying the mechanical properties of nuclear materials are compared. The presence of “outliers” in a sample of hardness values for hafnium ingots is studied with for fixed oxygen mass content. The situation of measurement error limitation without reliable information about its distribution is considered. The correctness of the application of numerical methods of interval analysis for processing experimental data under conditions of uncertainty and noisy experimental data is shown.